Changes in the properties of agrogray forest soils of the Udmurt Republic as a result of their long-term use in agricultural production - A. V. Lednev; A. V. Lozhkin; I. M. Kudryavtsev (Аграрная наука Евро-Северо-Востока, 2024)
Changes in the morphological and agrochemical parameters of agrogray forest soils over a fifty-year period of agricultural use were identified based on data from a monitoring survey of the soil cover of the Udmurt Republic. The studies were conducted on reference plots and based on soil survey data over an area of more than 9 thousand hectares. It was established that the fertility level of agrogray forest soils depended on their genetic characteristics (origin) and agricultural technology used on land plots. Throughout the observation period, agrogray forest soils were well differentiated by fertility level into three subtypes: dark gray (humus content – more than 5 %, sum of exchangeable bases – more than 35 mmol/100 g, soil reaction – close to neutral or neutral), light gray (2.5–3.5 %; 20–30 mmol/100 g; slightly acidic or close to neutral) and gray (the above mentioned indicators occupied an intermediate position). During the observation period, the properties of agrogray forest soils changed as follows: the thickness of the arable layer increased by an average of 2–4 cm, the humus content in the arable layer decreased by 0.2–0.3 abs.%, or 2.5–10.0 rel.%, and the soil became acidified within the initial grouping of soils according to the degree of acidity. The content of nutrients did not depend on the genetic characteristics of the soils, but was determined by the level of agricultural technology on the land plots. The identified patterns will make it possible to make a long-term forecast of further changes in these soils as a result of their agricultural use in order to develop measures to restore fertility.